The Exposure of Pb to Hair and Nails in Children Around "X” Coal Mines Using Atomic Absorption Spectroscopy (AAS) Method - Tri Ana Mulyati; Fery Eko Pujiono; Indah Indah (JURNAL KESEHATAN LINGKUNGAN, 2021)
Introduction: The exposure of Pb from coal mining activity could be accumulated primarily in the hair and nails. It was a presence as a bioindicator of Pb contamination in the community. Children who lived around coal mining were also likely to experience contamination of Pb. The children could absorb up to 50% of Pb metal. Methods: This study used a cross-sectional design. The sample was taken using cluster sampling and classified based on the age group, namely 1-3 years, 4-6 years, and 7-9 years. Exposed respondents lived around 1-10 kilometers from the mining area, and the non-exposed respondents lived outside. Some hair and nails would be taken from all respondents, which were sent to a laboratory directly. Atomic Absorption Spectroscopy was used to measure the levels of Pb. Results and Discussion: This study showed that Pb levels in the hair of exposed respondents in all age categories were above the WHO threshold limits value (â‰¤ 12µg/g). In addition, in nails, Pb levels exceed the threshold limits value in the exposed sample groups 4-6 years and 7-9 years. Differences in Pb levels in the hair and nails between exposed dan non-exposed respondents showed significantly by the statistical test. Conclusion: Communities living in coal mining areas are at greater risk of exposure to heavy metals than others. Pb is one type of heavy metal that accumulates in the body, specifically in hair and nails, because it did not release by metabolism. Hence, it becomes a bioindicator to ensure our entire body exposure to hazardous materials.